2017
DOI: 10.2147/ott.s124134
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic values of contrast-enhanced ultrasound in breast cancer: a retrospective study

Abstract: This study aimed to explore the diagnostic and prognostic values of contrast-enhanced ultrasound (CEUS) in breast cancer. Between September 2009 and October 2011, a total of 143 breast cancer patients and 161 healthy people were selected as case group and control group, respectively. After the identification of lesions by conventional ultrasound, all patients underwent CEUS. The CEUS images were analyzed, and time–intensity curves (TICs) were obtained. Hematoxylin–eosin and immunohistochemistry staining was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…It is probable that angiogenic factors produced by more aggressive ER negative tumors, along with rapid growth of these tumors, result in blurred lesion margins in CEUS. Absence of ER expression has already been related to other qualitative and quantitative CEUS characteristics in literature, like more common perfusion defects (14,15,17) or centripetal enhancement (15), as well as higher PEAK intensity (13). To illustrate, perfusion defects are the result of rapid growth and active metabolism of malignant tumors, leading to insufficient vascular formation and nutrition supply and finally to central hypoxia and necrosis (38).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…It is probable that angiogenic factors produced by more aggressive ER negative tumors, along with rapid growth of these tumors, result in blurred lesion margins in CEUS. Absence of ER expression has already been related to other qualitative and quantitative CEUS characteristics in literature, like more common perfusion defects (14,15,17) or centripetal enhancement (15), as well as higher PEAK intensity (13). To illustrate, perfusion defects are the result of rapid growth and active metabolism of malignant tumors, leading to insufficient vascular formation and nutrition supply and finally to central hypoxia and necrosis (38).…”
Section: Discussionmentioning
confidence: 95%
“…All the same, histologic grade has already been correlated with other qualitative CEUS characteristics in literature. To illustrate, Colpaert et al (37) found that tumors of higher histologic grade are more susceptible to central necrosis than tumors of lower histologic grade, while other researchers correlated penetrating vessels and perfusion defects with grade III tumors (14,15,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations